Social Construction for Maintaining Local Wisdom: Study of Kajang Community, South Sulawesi, Indonesia - Jalal, Jalal; Akhiruddin, Akhiruddin; Salemuddin, Muh. Reski; Iskandar, Abdul Malik; Sriwahyuni, Sriwahyuni; Kasim, Hasanudin (JSW (Jurnal Sosiologi Walisongo), 2024)
The Kajang people are known for their lives based on traditional values, traditional beliefs, and distinctive local wisdom. They are here to preserve traditions amidst the blows of globalization. With this local wisdom, researchers are interested in analyzing the social construction of the Kajang traditional community to maintain their local wisdom. This research used a qualitative approach through participant observation, in-depth interviews, and data analysis using grounded theory analysis techniques. The research results show that the Kajang indigenous community faced challenges in maintaining their local wisdom amidst social changes and external influences. However, with its social construction, it maintained local wisdom through externalization, objectivation, and internalization processes. With this social construction approach, the Kajang traditional community can show resilience and initiative to preserve local wisdom and strengthen social ties between community members. This research will not only provide new insights into the local wisdom of the Kajang people in efforts to preserve culture, community development, and policy development in Indonesia.